Pendampingan Pengawasan Mutu dan Pembuatan Merk Produk Sabun Cuci Piring Pada Kelompok Dasa Wisma Desa Mulyoagung Kecamatan Dau Kabupaten Malang - Ida Nuraini; Rahmad Hidayat (Program Studi Ekonomi Pembangunan, 2025)
The dishwashing liquid produced by the Dasa Wisma Bougenvile 5B Group in Mulyoagung Village, Dau District, Malang Regency has not yet been accepted by semi-modern and modern stores due to the absence of a brand and unstable product quality in terms of color, thickness, and foam content. This mentoring activity aims to improve product quality to meet standardized criteria and assist in brand development so that the product is more marketable and receives fewer consumer complaints. The implementation method began with a seminar on the importance of quality control and brand development strategies, followed by hands-on practice in quality control techniques and brand creation, and concluded with an evaluation of production outcomes. The results showed high enthusiasm from all group members during the activities. Participants gained knowledge about quality control, the importance of branding, and brand building strategies. Based on group consensus, the product was branded “Starlight” and a previously non-existent quality control team was formed. Evaluations conducted over eight production cycles showed stable results without consumer complaints. However, stores provided suggestions to equip the product with a barcode and obtain legal certifications such as the Household Health Supplies (PKRT) license from the Ministry of Health and halal certification to expand market reach.